Relationship between glycated haemoglobin and fasting plasma glucose among diabetic out-patients at the University Teaching Hospital, Lusaka, Zambia - Musenge, Emmanuel M.; Manankov, Alexey; Michelo, Charles; Mudenda, Boyd (Tanzania Journal of Health Research, 2016)
Background: Glycated haemoglobin (HbA1c) measurement provides an accurate result of glycaemic levels from blood drawn at any time of day without reference to prandial state. We established the relationship between HbA1c and fasting plasma glucose (FPG) in diabetic out-patients among diabetic outpatients in Lusaka, Zambia. Methods: This cross-sectional study was carried out at the University Teaching Hospital diabetic clinic, Lusaka, Zambia. A total sample of 198 consenting participants was selected randomly from diabetic out-patients between September and December 2013. A structured interview schedule was used to capture data on socio-demographics and laboratory examination results. The Pearson’s correlation coefficient, Student’s t-test and Paired Samples t-test were used for data analysis. Results: A total of 198 patients (mean age+SD= 53.19±13.32 years) were involved in the study. Majority (60.10%) of the patients were females while 39.90 per cent were males. The mean±SD of FPG of the patients slightly increased from the previous 10.75±7.78 mmo/L to the current 11.09±6.23 mmo/L (p = 0.592). The mean±SD of HbA1c of the patients was 54.77±17.12 mmol/mol. There was a statistically significant weak and moderate positive correlation between HbA1c and the previous and current FPG (r = 0.282, P = 0.001 and (r = 0.385, p = 0.001), respectively. However, there was a statistically significant but weak negative correlation between HbA1c and age (r = -0.163, p = 0.023). Conclusion: We found evidence of an association between HbA1c and FPG proposing that as the FPG levels increase, the HbA1c levels also increase in a predictable way. There is need to sensitise more especially the major stakeholders in the management of diabetes mellitus to consider FPG as an alternative in glycaemic control monitoring in the absence of HbA1c.